2012
DOI: 10.1590/s0031-10492012002500001
|View full text |Cite
|
Sign up to set email alerts
|

A new dwarf species, new distribution records, and supplementary descriptive notes of the centipede genus Ityphilus Cook, 1899 (Chilopoda: Geophilomorpha: Ballophilidae) from central Amazonia, Brazil

Abstract: A new dwarf species of the centipede genus Ityphilus Cook, 1899, named I. donatellae sp. nov. (Chilopoda: Geophilomorpha: Ballophilidae) is hereby proposed on the basis of specimens from the vicinity of Manaus, Central Amazonia (Brazil), previously identified as Ityphilus calinus Chamberlin, 1957 (hereby designated holotype female, paratype male and paratype female). Supplementary morphological data and new illustrations are provided after this type material. The new species, characterized by having the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…A few early and mid-twentieth-century studies on Brazilian centipedes reported geophilomorphs (Brölemann 1909; Chamberlin 1914, Bücherl, 1940, 1942), but more recent studies tended to focus on Amazonian fauna (Calvanese and Brescovit 2017, Foddai et al 2002, Pereira 2012, 2013, Pereira et al 1994, 1995, 2000). The first geophilomorph records in Brazilian caves are from limestone caves in Mato Grosso do Sul (Dessen et al 1980) and São Paulo (Gnaspinni and Trajano 1994, Trajano 1987).…”
Section: Resultsmentioning
confidence: 99%
“…A few early and mid-twentieth-century studies on Brazilian centipedes reported geophilomorphs (Brölemann 1909; Chamberlin 1914, Bücherl, 1940, 1942), but more recent studies tended to focus on Amazonian fauna (Calvanese and Brescovit 2017, Foddai et al 2002, Pereira 2012, 2013, Pereira et al 1994, 1995, 2000). The first geophilomorph records in Brazilian caves are from limestone caves in Mato Grosso do Sul (Dessen et al 1980) and São Paulo (Gnaspinni and Trajano 1994, Trajano 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Worth noting is that most of these cases are known within the Schendylidae, e.g. in the single species of Falcaryus Shinohara, 1970 and in some species of Ityphilus from South America (Shinohara, 1970;Pereira, 2012Pereira, , 2013b, but only weakly resembling those of Dinogeophilus. The peculiar denticles of Dinogeophilus may therefore represent an evolutionary novelty of this lineage.…”
Section: Miniaturization Paedomorphosis and Evolutionary Novelties In Dinogeophilusmentioning
confidence: 99%
“…11). Es posible que su afinidad geográfica sea a la zona neártica porque posee el borde interno de los tarsungula forcipulares liso, en lugar del borde interno aserrado observado en la mayoría de las especies neotropicales (Pereira, 2012).…”
Section: Ityphilus Cifuentesi Sp Novunclassified
“…Es muy poco lo que se conoce sobre el hábitat de las especies incluidas en el género Ityphilus; sin embargo, de las 21 especies de Ityphilus descritas para la región Neotropical, la mayoría se ha registrado en la Amazonia Central, un bosque lluvioso tropical (Pereira, 2013) con zonas inundables, pastizales transformados por el hombre, bosques altos no inundables (Adis, 2002), así como bosques secundarios (Pereira, 2012). En lo que se refiere a las 2 especies: I. lilacinus Cook, 1899 e I. cavernicolus (Matic et al, 1977), se encontraron en cuevas de Cuba; en cuanto a I. idanus Crabill, 1960, se registró en una cueva en Barbuda (Crabill, 1960;Matic et al, 1977).…”
Section: Introductionunclassified